2022
DOI: 10.1136/bmjopen-2021-060246
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor expression in patients with cardiac arrest in the early period after the return of spontaneous circulation: a prospective observational single-centre study

Abstract: ObjectivesRapid changes in glucocorticoid (GC) levels and adrenal insufficiency are related to the development of post-cardiac arrest (CA) syndrome. However, GC receptor (GR) expression changes have not been studied. Hence, this study aimed to investigate the association of early changes in GR expression and prognosis and immune response in patients who experienced CA.DesignProspective observational study.SettingEmergency department.ParticipantsPatients (85) in the early period of return of spontaneous circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Consequently, prolonged ischemia time (followed by reperfusion) is associated with greater, intracellular, oxidative stress [ 13 ], and likely, more extensive oxidation and loss of function [ 12 ] of various proteins, including the GR. Accordingly, a recent study reported rapid, post-ROSC decline in B/T lymphocyte GR-expression [ 14 ].…”
Section: Multi-level Vse Effects In Ihcamentioning
confidence: 99%
“…Consequently, prolonged ischemia time (followed by reperfusion) is associated with greater, intracellular, oxidative stress [ 13 ], and likely, more extensive oxidation and loss of function [ 12 ] of various proteins, including the GR. Accordingly, a recent study reported rapid, post-ROSC decline in B/T lymphocyte GR-expression [ 14 ].…”
Section: Multi-level Vse Effects In Ihcamentioning
confidence: 99%
“…These steroids appear to lower inflammation by decreasing pro-inflammatory cytokines [ 60 , 61 ]. Further, a prospective observational single-center study focused the immune responses and glucocorticoid receptor expression in patients with CA [ 62 ]. The study revealed that CA survivors exhibit lower glucocorticoid receptor levels in leukocytes, especially those with prolonged CA and adverse neurological outcomes, linking receptor downregulation with increased inflammation [ 62 ].…”
Section: Human Studies Aiming To Regulate Excessive Immune Responses ...mentioning
confidence: 99%
“…Further, a prospective observational single-center study focused the immune responses and glucocorticoid receptor expression in patients with CA [ 62 ]. The study revealed that CA survivors exhibit lower glucocorticoid receptor levels in leukocytes, especially those with prolonged CA and adverse neurological outcomes, linking receptor downregulation with increased inflammation [ 62 ]. This suggests that early post-CA corticosteroid therapy might help regulate immune responses and improve patient outcomes by normalizing glucocorticoid receptor activity.…”
Section: Human Studies Aiming To Regulate Excessive Immune Responses ...mentioning
confidence: 99%